Proceso de salida de las mujeres de la violencia doméstica : comportamiento resiliente (2012)
ABSTRACT: To understand the process to leave of the women of the domestic violence. Methodology: qualitative study realized between February, 2001 and October, 2004; based on the Founded Theory; were interviewed in depth 18 adult women living in Medellin (Colombia) and carrying at least one year of leaving domestic violence. Results: It was a process led by women, supported on introspection and selfconsciousness. It involved overcoming fear, review the traditional gender stereotype and give the identity of the victim, to reconstruct the identity. In interaction with the social support network they developed resilient factors, essential for the successful outcome of mistreatment as: responsibility, persistence in the determination of leave abuse, self-esteem, self-confidence, sociability, optimism, curiosity and spirituality. Conclusions: The output is a personal decision; a difficult, long, painful and complex process. Resilience promotes human development as women are strengthened as subjects of law, rebuild identity and gain freedom. Social solidarity is indispensable for building resilient behavior. Of the 18 female participants, only three -16.6% - were couples who changed their behavior, requesting and receiving therapeutic help. It is unlikely that violent men change their behavior without seeking help.